A positive feedback loop between mTORC1 and cathelicidin promotes skin inflammation in rosacea - Zhili Deng; Mengting Chen; Yingzi Liu; San Xu; Yuyan Ouyang; Wei Shi; Dan Jian; Ben Wang; Fangfen Liu; Jinmao Li; Qian Shi; Qinqin Peng; et al. (EMBO Molecular Medicine)
Abstract Rosacea is a chronic inflammatory skin disorder whose pathogenesis is unclear. Here, several lines of evidence were provided to demonstrate that mTORC1 signaling is hyperactivated in the skin, especially in the epidermis, of both rosacea patients and a mouse model of rosacea‐like skin inflammation. Both mTORC1 deletion in epithelium and inhibition by its specific inhibitors can block the development of rosacea‐like skin inflammation in LL37‐induced rosacea‐like mouse model. Conversely, hyperactivation of mTORC1 signaling aggravated rosacea‐like features. Mechanistically, mTORC1 regulates cathelicidin through a positive feedback loop, in which cathelicidin LL37 activates mTORC1 signaling by binding to Toll‐like receptor 2 (TLR2) and thus in turn increases the expression of cathelicidin itself in keratinocytes. Moreover, excess cathelicidin LL37 induces both NF‐κB activation and disease‐characteristic cytokine and chemokine production possibly via mTORC1 signaling. Topical application of rapamycin improved clinical symptoms in rosacea patients, suggesting mTORC1 inhibition can serve as a novel therapeutic avenue for rosacea.